2003
DOI: 10.1164/rccm.200207-710oc
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Component of Airway Remodeling in Asthma Is Reduced by High Dose of Fluticasone

Abstract: We conducted a randomized, double-blind, parallel-group study to assess the effect of 6 weeks treatment with low-dose (100 microg twice a day) or high-dose (500 microg twice a day) inhaled fluticasone propionate (FP) on the vascular component of airway remodeling in 30 patients with mild to moderate asthma. We also studied the effect on the inflammatory cells and the basement membrane thickness, and we compared findings from bronchial biopsies taken in patients with asthma with those in eight control subjects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
152
1
11

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(174 citation statements)
references
References 36 publications
10
152
1
11
Order By: Relevance
“…Preincubation of basophils with high concentrations of the agonist is known to cause desensitization to a subsequent challenge with the same stimulus (23,27). We examined the relationship between VEGF-A 165 and eotaxin or Hp (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) by evaluating the effects of heterologous desensitization between these stimuli on basophil chemotaxis. Purified basophils were preincubated with buffer or with VEGF-A 165 (500 ng/ml) or eotaxin (100 ng/ml) or Hp (2-20) (500 nM) in P-EDTA for 1 h at 37°C.…”
Section: Heterologous Desensitization Between Vegf-a 165 and Eotaxin mentioning
confidence: 99%
See 2 more Smart Citations
“…Preincubation of basophils with high concentrations of the agonist is known to cause desensitization to a subsequent challenge with the same stimulus (23,27). We examined the relationship between VEGF-A 165 and eotaxin or Hp (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) by evaluating the effects of heterologous desensitization between these stimuli on basophil chemotaxis. Purified basophils were preincubated with buffer or with VEGF-A 165 (500 ng/ml) or eotaxin (100 ng/ml) or Hp (2-20) (500 nM) in P-EDTA for 1 h at 37°C.…”
Section: Heterologous Desensitization Between Vegf-a 165 and Eotaxin mentioning
confidence: 99%
“…Angiogenesis is critical for such chronic inflammatory disorders as rheumatoid arthritis (3), bronchial asthma (4,5), and tumor growth (6). Vascular endothelial growth factor (VEGF) 3 is the most potent proangiogenic mediator known so far.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a cross-sectional study, therapy with high doses (≥ 800 µg/day) of beclomethasone dipropionate was associated with a reduced vascular area of the lamina propria [38]. In interventional studies, beclomethasone dipropionate (800 µg/day) therapy for 6 months reduced the number of blood vessels and the vascular area [39], whereas a 6-week treatment with fluticasone propionate was effective at 1000 µg/day inhaled dose in reducing the number of blood vessels and the vascular area [29].…”
Section: Delayed Effects On Airway Blood Flowmentioning
confidence: 94%
“…A number of studies have also demonstrated increased vascularity (i.e. size and number of vessels, or cross-sectional vascular area) of the bronchial mucosa in patients with asthma compared with healthy controls [28,29].…”
Section: Airway Blood Flow In Asthmamentioning
confidence: 99%